Optimalisasi Kesehatan Masyarakat Melalui Kegiatan Terintegrasi dan Edukasi Kesehatan Terpadu - Rokhan, Muhammad Nurkholis; Arya, Krishna; Anataya, Ivana; Naufaldy, Aqillah Nabil; Achmadi, Rahma Amalina; Azizah, Citra Yuridha Nur; Adittya, Yudha Wisnu; Pranowo, Galih Yudo; Rahmawati, Suci Nur; Rahayu, Galuh Kurniawati; Sundari, Sri (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity aims to optimize public health in the Celep Hamlet through integrated health education and activities. It addresses health issues arising from a lack of understanding and utilization of healthcare facilities, while also maximizing the potential of local natural resources such as Rosella. Using a participatory approach, the program includes education on non-communicable diseases, training on cultivating and processing Rosella into tea and soap, digital marketing education, and used cooking oil waste management. Each session involved approximately 20 participants and lasted for 90 minutes. The results showed a significant increase in community knowledge, with post-test scores averaging 90% in the Rosella tea workshop and 88.89% in the soap workshop, indicating the program’s success in improving community health and self-reliance.